Assessing road criticality and loss of healthcare accessibility during floods: the case of Cyclone Idai, Mozambique 2019 - Petricola, Sami; Reinmuth, Marcel; Lautenbach, Sven; Hatfield, Charles; Zipf, Alexander (International journal of health geographics, 2022)
The ability of disaster response, preparedness, and mitigation efforts to assess the loss of physical accessibility to health facilities and to identify impacted populations is key in reducing the humanitarian consequences of disasters. Recent studies use either network- or raster-based approaches to measure accessibility in respect to travel time. Our analysis compares a raster- and a network- based approach that both build on open data with respect to their ability to assess the loss of accessibility due to a severe flood event. As our analysis uses open access data, the approach should be transferable to other flood-prone sites to support decision-makers in the preparation of disaster mitigation and preparedness plans.
Gesehen am 21.12.2022